An Evaluation of Determinants Influencing Employee Adherence to Personal Protective Equipment (PPE) Usage in Mitigating Occupational Accident Risks within a Manufacturing Firm in Batam - Mulyana, Andi Erna; Sinaga, Ledy Bagindayana (Pusat P2M Politeknik Negeri Batam, 2024)
This study aims to examine the factors influencing employee adherence to the use of Personal Protective Equipment (PPE) within a private manufacturing company in Batam. The study population consists of all production department employees at the company, totaling 87 respondents. A quantitative research design was employed, utilizing a cross-sectional approach and correlation analysis. The relationship between independent variables